Evidence and potential risk factors of tuberculosis among captive - Yusof Yakubu; Bee Lee Ong; Zunita, Z.; Latifah Hassan; Abdul Rahim Mutalib; Yun Fong Ngeow; Khebir Verasahib; Mohd Firdaus Ariff Abdul Razak (2016)

(untitled)
Elephant tuberculosis (TB) caused by Mycobacterium tuberculosis is an important re-emerging zoonosis